Cyclodextrin reduces cholesterol crystal uptake by circulating monocytes in patients undergoing coronary angiography - Nikola Lübbering; Alexander Krogmann; Felix Jansen; Eicke Latz; Georg Nickenig; Sebastian Zimmer (PLoS ONE, 2025)
Background Atherosclerosis is a chronic inflammatory disease driven by endothelial dysfunction, cholesterol accumulation, and immune activation leading to thrombosis and vascular stenosis. While LDL-lowering therapies are firmly established, targeting the underlying inflammation is still an emerging strategy. Cholesterol crystals (CC) contribute to inflammation by activating the NLRP3 inflammasome in monocytes and promoting disease progression. Cyclodextrin (CD), an FDA-approved drug carrier, has shown atheroprotective effects by enhancing cholesterol metabolism and reducing inflammation in preclinical models. This study investigated whether CC-uptake in human monocytes, a prerequisite for inflammasome activation, is also influenced by CD pretreatment. Methods Human peripheral mononuclear cells were isolated from whole blood samples provided by 76 patients undergoing coronary angiography at the University Hospital Bonn between November 2017 and February 2018. After separation, peripheral mononuclear cells were stimulated with 2-Hydroxypropyl-γ-Cyclodextrin and CC. CC-uptake by monocytes was analyzed using flow cytometry. Results CC-uptake by monocytes varied greatly between patients (8–37%), with lower uptake observed in patients with elevated leukocytes ( p = 0.0058) and diabetes mellitus ( p = 0.0448). CD-pretreatment significantly reduced CC-uptake (20.1% ± 0.8% vs. 15.0% ± 0.6%, p < 0.0001). Interindividual variability in CD response (CCΔCD) was noted; 40 patients exhibited a significant reduction in CC-uptake, while nine showed an increase. Patients with coronary artery disease (CAD) ( p = 0.0316), requirement for percutaneous coronary intervention (PCI) ( p = 0.0030), and elevated leucocyte levels ( p = 0.0135) had lower CCΔCD, suggesting a link between systemic inflammation and attenuated CD efficacy. Conclusion We demonstrated that CD significantly reduced CC-uptake in patients undergoing coronary angiography, which supports its role in inhibiting CC-phagocytosis and promoting cholesterol efflux. Interestingly, patient response to CD varied, with those exhibiting greater systemic inflammation or CAD showing a less pronounced reduction in CC-uptake. Our findings provide insight into the atheroprotective mechanisms of CD and suggest its potential utility in evaluating individual cardiovascular risk and monitoring CD-based therapeutic interventions in humans.